Knee Pain due to Loose body in the Knee Joint: A Case Report in Dr. Kariadi General Hospital Semarang: Knee Pain due to Loose body in the Knee Joint: A Case Report in Dr. Kariadi General Hospital Semarang - Novriansyah, Robin; Kusuma, Faizurrahman Andi (Medica Hospitalia : Journal of Clinical Medicine, 2022)
BACKGROUND: Loose Bodies are fragments consisting of cartilage or bone that move freely in the joint space. The occurrence of Loose Bodies associated with OCD is considered a rare case in Indonesia. The presence of Loose Bodies can cause several symptoms such as pain and resistance to extension and flexion of the knee joint. The presence of an impinging osteophyte in the lateral condyle of the femur, and a pedunculated osteophyte, can provide a clinical feature similar to Loose Bodies. Good anamnesis, physical examination, and diagnosis for correct management can provide a good outcome. OBJECTIVE: To provide an overview regarding diagnosis in loose body cases and arthroscopy debridement therapy in loose body cases in the knee joint. CASE: A 42-year-old man was presented with chronic pain in the left knee and limited left knee flexion since 3 years prior. Initially, the patient was diagnosed with grade 2 genu joint osteoarthritis with osteophytes in the lateral condylus. Anamnesis and physical examination were performed at dr. Kariadi General Hospital Semarang. X-photo showed a picture of the Loose Bodies. A debridement arthroscopy was performed. 8 weeks of follow-up no pain, no resistance in flexion and extension, KOOS Score from 18.6 to 92.3. CONCLUSION: It is advised to remove loose body in knee joint through arthroscopy debridement. Loose bodies should always undergo thorough workup to determine the diagnosis and treat the patient accordingly. KEYWORDS: Knee pain, loose body, osteochondritis dissecans, arthroscopy debridement